IDENTIFIKASI AWAL BENTUK-BENTUK KERUSAKAN TANAMAN LINGGUA (Pterocarpus indicus, Wild) DI PESEMAIAN - Wattimena, Cornelia (PT. BARRINGTONIA ASIATICA LESTARI, 2024)
This research aims: as an initial observation, symptoms and signs of damage due to insect attacks or disease on linggua plants in the nursery. The research was carried out at the People's Nursery (KBR) nursery in Liliboi Village, West Leihitu District, Central Maluku Regency, in October 2022. This research included observations of various damages to linggua plants in the nursery at KBR in Liliboi village. Observations were carried out in detail. on leaves, twig shoots and plant stems. Each type of damage is carried out by taking photos and recording the type of damage that occurs. The research results show that the pests and diseases that attack are grasshoppers and leaf spot disease. Grasshoppers can attack young and old plants by damaging the plants' leaves and shoots. Apart from that, grasshoppers have long legs so they can jump very quickly from one plant to another, grasshoppers are poly fat animals. Leaf spot disease has a characteristic, the formation of dead areas on the leaves (necrotic) with varying sizes ranging from small to large, round to angular or irregular which do not die completely unless a number of spots merge together and form large spots, so that the leaf tissue dies.